Distribution, Metabolism, and Recovery of Resin Acids in the Intestine and Tissues of Broiler Chickens in a Feeding Trial With Tall Oil Fatty Acid-Supplemented Diets - Apajalahti, Juha; Vienola, Kirsi; Raatikainen, Kari; Kettunen, Hannele; Vuorenmaa, Juhani (Frontiers in Veterinary Science, 2020)
Tall oil fatty acids (TOFA) are novel, health-improving feed ingredients which have been shown to improve the performance of broiler chickens. TOFA contains resin acids, the suggested key components for its beneficial effects. For product safety, possible accumulation of TOFA components in tissues consumed by end-users is an issue of major importance. Wheat-soy-based diets with an indigestible marker and TOFA at 0, 750 and 3000 g/t were fed to broiler chickens for five weeks; 11 replicate pens/treatment. Deposition of resin acids was assessed by analyzing jejunal tissue, breast muscle, abdominal fat, blood, liver, bile and digesta along the intestinal tract at the end of the 35-day trial. Both free and conjugated resin acids were quantified. With TOFA 3000 g/t diet, 30% of ingested resin acids could not be recovered from jejunal digesta. Also, a proportion representing 45% of resin acids fed were in conjugated form and thus had already re-entered the intestine from the bile duct. This means that at least 75% of resin acids ingested had become absorbed in, or proximal to jejunum. Recovery of resin acids in excreta was 45% and 70% when TOFA was fed at 750 and 3000 g/t, respectively. Based on recovery data, of the estimated 1087 mg of resin acids ingested by birds on the high TOFA dose during their lifetime, about 330 mg was unaccounted for. In analysis of jejunal tissue, blood, liver, bile, breast muscle, and abdominal tissue, less than 1 mg of resin acids was found after the 35-day trial when TOFA at the four-fold the recommended dose was fed. It is likely that the host or microbiota mineralized or converted one-third of resin acids to a form that escaped analysis. TOFA at 3000 g/t dose caused no detectable adverse effects in broiler chickens. Based on analysis of breast meat and liver, the common edible tissues, a human consumer would ingest less than 100 g of resin acids in a single meal. That is one-thousandth of the dose shown to be harmless in rodents. Thus unintentional exposure of human consumers to resin acids is marginal, and posed no safety concerns.